SEORANG PENDERITA HAMIL DENGAN LEUKEMIA MIELOID AKUT - Sukrawan, Gede; Losen Adnyana, Wayan; Suega, Ketut (journal of internal medicine, 2012)
Leukemia during pregnancy is extremely rare, the estimate one per100,000 pregnancies each year. Intrauterine growth disorders have been reported in pregnant women with untreated AML. A pregnant female patient, 28 years old, Balinese, private employ came with chief complain fever, sweaty, nausea and vomiting, body weekly, Physical examination: anemic, pale, blood pressure; 120/80mmHg, pulse 88 x/minute, respiration 20 x/minute, axillary temperature of 36.7 degrees Celsius, heart andlung arenormal, Abdoment: fundus uteri-high processusxipoideus, distention and bowel sounds normal. Laboratory January 14th 2011: leukocyte 63,2 103/ul, Hb 11.7 g/dl, hematocrite 33.6%, MCV 30.7 pg, trombocite 40 103/ul, anatomicalpathology on November 26th 2009 with increasing blast dysplasia eritroid series, allowing a leukemia acute. January 16th 2010 chemotherapyAra-C 150 mg in 500 ml NaCl 0.9% 24 hours for 7 days and daunorubicine 60 mg IV bolus for 3 days. January 18th 2010 laboratory resultleukosit 46.2 x 103/ul, Hb 9.2 g/dl, hematocrite 26.3%, MCV 87.4 fl, MCH 30.4 pg and thrombocyte 10 x 103/ul. The patient had complite remission after chemoterapy and laboratory results on February 12th 2010 were leucocyte 7.02 x 103/ul, Hb 8.6 g/dl, hematocrite 25.5%, MCV 74.5 fl, MCH 25.5 and thrombocyte 125 x 103/ul. The baby was born with normal condition with operation. Acute leukemia in pregnancy should be managed together hematologist, obstetrics-gynaecology and neonatologists.
Keywords: AML, pregnancy, complete remission